The Outcome of Vaginal Birth After One Caesarean Section (VBAC) - Akter, Mst Jesmin; Shirin, Eliza (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Caesarean section has become the most performed major operation in obstetrics. The increasing rate of primary caesareans section becomes high worldwide due to early detection of fetal and maternal complications. Repeated caesarean section is one of the major contributory factors for increasing this rate very significantly. Now a day, vaginal delivery of pregnant mothers with the history of previous one caesarean with non-recurrent cause was established. It has been shown that the outcome of trial of labor in past caesarean delivery is acceptable, effective and safe for both mother and fetus, if the women are properly selected. Objective: The objectives of this study were to determine the outcomes of vaginal birth after caesarean section (VBAC) in case of previous one caesarean section to reduce the subsequence cesarean section with its complication. Materials and Methods: It was a cross sectional study carried out in the Maternity Unite-1, Department of Gynecology & Obstetrics, Sir Salimullah Medical College and Mitford hospital, Dhaka, Bangladesh, held on January 2010 to December 2010. Out of total 380 admitted pregnant women who had previous one caesarean section, 50 pregnant women of 37-42 weeks of gestational age with the history of one caesarean delivery with alive baby were selected as study population following consecutive and purposive sampling method. Patients with spontaneous onset labor but preterm pregnancy with any contraindication or prior caesarean section due to recurrent causes, history of classical caesarean section, more than one caesarean section, multiple pregnancy, pregnancy with medical disorder were excluded in the study. Results: Out of total 50 sampled pregnant women, vaginal delivery were done 16(32%) & emergency cesarean section were done 34(68%). According to the age group both vaginal & cesarean section 20- 30 years were predominant, which were 8(50%) and 17(50%) respectively. Regarding antenatal care 13(81.25%) of vaginal delivery cases were regular. On the other hand, only 10(29.41%) of cesarean section were regular in care. Fetal survival outcome in vaginal & caesarean were 14(87.5%) and 33(97.05%) respectively. Comparing the maternal complication maximum number of vaginal delivery group had no complications. Conclusion: It has been seen in this study that good antenatal care is of paramount importance and was associated with higer rate of vaginal delivery is pregnancy with history of one caesarean section. In this series the post Partum hemorrhage was higher in vaginal delivery group and wound infection rate was high in caesarean group. J Bangladesh Coll Phys Surg 2021; 39(1): 36-45